Reservoir Simulator For Improved Recovery Of Coalbed Methane (Icbm) Part Ii : Effect Of Coal Matrix Swelling And Shrinkage - Ego Syahrial (Testing Center for Oil and Gas LEMIGAS, 2009)
Sequestration of CO2 in deep unmined coal seams is currently under development for improved recovery of coalbed methane (ICBM) as well as permanent storage of CO2. Recent studies have shown that CO2 displaces methane by adsorbing more readily onto the coal matrix compared to other greenhouse gases, and could therefore contribute towards reducing global warming. In order to carry out a more accurate assessment of the potential of ICBM and CO2 sequestration, field based numerical simulations are required. Existing simulators for primary CBM (coalbed methane) recovery cannot be applied since the process of CO2 injection in partially desorbed coalbeds is highly complex and not fully understood. The principal challenges encountered in numerical modelling of ICBM/CO2 sequestration processes which need to be solved include: (1) two-phase flow, (2) multiple gas components, (3) impact of coal matrix swelling and shrinkage on permeability, and (4) mixed gas sorption. This part II of this two-part paper series describes the development of a compositional simulator with the impact of matrix shrinkage/swelling on the production performance on primary and echanced recovery of coalbed methane. The numerical results for enhanced recovery indicate that matrix swelling associated with CO2 injection could results in more than an order of magnitude reduction in formation permeability around the injection well, hence prompt decline in well injectivity. The model prediction of the decline in well injectivity is consistent with the reported field observations in San Juan Basin USA. Also, a parametric study is conducted using this simulator to investigate the effects of coal properties on the enhancement of methane production efficiency based on published data.